The Role of Government Regulations in Lieu of Law as a Constitutional Instrument for Responding to Economic Crises: Realizing Legal Certainty and National Stability in Indonesia - Elen Setiadi (Journal of Legal and Cultural Analytics, 2026)
This article aims to analyze the role of the Government Regulation instead of Law (Perppu) as a constitutional instrument in responding to the economic crisis to achieve legal certainty and national stability in Indonesia. The research uses a normative juridical method with a statutory and conceptual approach, supported by an analysis of laws and regulations, Constitutional Court decisions, and relevant legal doctrines. The results show that the Perppu is a legal instrument that has constitutional legitimacy based on Article 22 of the 1945 Constitution of the Republic of Indonesia to address urgent situations, including the economic crisis. The implementation of the Government Regulation in place of Law Number 1 of 2020, which was later stipulated as Law Number 2 of 2020, proves that the Perppu can support fiscal and financial system stability, although it still raises debates regarding the limits of the President's authority, the mechanism of checks and balances, and the protection of citizens' constitutional rights. This study concludes that the use of a Perppu must remain grounded in the principles of the rule of law, legal certainty, proportionality, accountability, and constitutional supremacy to be an effective instrument for addressing the economic crisis while maintaining national stability.